Sémantique formelle: Volume 1 Introduction à la grammaire de Montague - Roussarie, Laurent (Textbooks in Language Sciences, 2017)
"For nearly half a century formal semantics has been a prominent area in linguistic theory, developed in a fruitful collaboration among linguists, logicians and philosophers. Formal semantics is sometimes regarded with reluctance (even dreaded) due to its mathematical precision and the apparent complexity of its symbolism. This textbook -the first one of this scope in French- provides a relaxed self-contained introduction to the domain, allowing the reader autonomous progressive study from the basic central concepts to significant innovations that have shaped the domain since Montague's seminal work. Through its chapters, the book provides acquaintance with elements of scientific methodology generally used in formal semantics. The six chapters, completed with solved exercises, gradually move from basic notions in logic and model-theoretic semantics, to quantification, temporal and modal logic, intensionality, and typed λ-calculus, culminating in compositional semantic analysis at the syntax-semantics interface. This introduction will be supplemented with a second volume that would focus on applications and advances in the field which extend the scope of the formalism. The book is intended for linguistics undergraduate and postgraduate students and researchers wishing to improve their skills in formal semantics, as well as for students and researchers of other domains, such as philosophy, logic, or computational science."